Intervalo de segurança da aplicação de Metsulfuron-methyl usado em dessecação e posterior cultivo da soja - Silva, Jessica Dias Gomes da (2020)
Soybean is a crop of extreme economic and social importance worldwide, and the incidence of weeds is one of the main factors that interfere in the crop's productivity. The control of soybean weed with the application of herbicides is the main management method used by producers, due to the practicality, efficiency, speed and lower cost when compared to other control methods. However, the inappropriate use of these products, associated with the lack of new molecules, has hampered the success of this practice. The use of different herbicides by producers has been the alternative found in control programs. However, for the effectiveness of herbicides it is necessary to know the molecule used in order to avoid possible damage to the crop. The objectives of this study were: i) to evaluate the interference of the herbicide metsulfuron-methyl applied at different times on the development of soybean cultivated in soils with different characteristics; ii) to study the effects of doses of the herbicide metsulfuron-methyl applied at different times on the physiological and productive traits of soybean cultivar NA 5909 RG; iii) to evaluate the effects of metsulfuron-methyl in a cucumber bioindicator plant. Experiments were carried out in a greenhouse and in the field, both conducted in a randomized block design in a factorial scheme. In greenhouse, different application times (0.15, 30 and 45 days before sowing) and soils from different locations (Erechim, Itaqui, Piratini and Santa Maria) were evaluated. For the field experiment, the effect of seasons (0.15, 30 and 45 days before sowing) and metsulfuron-methyl doses (0.0; 3.6; 5.4; 7.2 and 9.0 g ha-1 i.a.), which was repeated for two consecutive years. The last experiment was also carried out in greenhouse with cucumber plants, as a bioindicator, collecting test soil that was installed in the field. Phytotoxicity, physiological and morphological traits and yield components were evaluated. It can be seen that the Erechim soil provided the least soybean growth and development, the proximity of the application of the herbicide to the soybean sowing caused damage to the crop, which were more expressive in the highest dose. Physiological and phytotoxicity damages were also observed in cucumber plants.